HIV-1 subtype B-infected MSM may have driven the spread of transmitted resistant strains in France in 2007–12: impact on susceptibility to first-line strategies. (26th February 2015) - Frange, Pierre; Assoumou, Lambert; Descamps, Diane; Chéret, Antoine; Goujard, Cécile; Tran, Laurent; Gousset, Marine; Avettand-Fenoël, Veronique; Bocket, Laurence; Fafi-Kremer, Samira; Guinard, Jerome; Morand-Joubert, Laurence; et al.
Abstract: Background: Our study describes the prevalence of transmitted drug resistance (TDR) among 1318 French patients diagnosed at the time of primary HIV-1 infection (PHI) in 2007–12. Methods: HIV-1 resistance-associated mutations (RAMs) were characterized using both the 2009 WHO list of mutations and the French ANRS algorithm. A genotypic susceptibility score was estimated for each first-line recommended ART combination. Results: Patients were mainly MSM (72.6%). Non-B variants were identified in 33.7% of patients. The proportion of TDR was estimated as 11.7% (95% CI 10.0–13.5). The prevalences of PI-, NRTI-, first-generation NNRTI and etravirine/rilpivirine-associated RAMs were 2.5%, 5.2%, 3.9% and 3.2%, respectively. Single, dual and triple class resistance was found in 9.6%, 1.0% and 1.1% of cases, respectively. Additionally, 5/331 strains isolated in 2010–12 had integrase inhibitor (II)-related RAMs (isolated E157Q mutation in all cases). TDR was more common among MSM than in other groups (12.9% versus 8.6%, P  = 0.034), and in case of B versus non-B subtype infections (13.6% versus 7.9%, P  = 0.002). The proportions of fully active combinations were ≥99.2%, ≥97.3% and ≥95.3% in cases of PI-, II- and NNRTI-based regimens, respectively. In 2010–12, the proportion of fully active efavirenz-based ART was lower in cases of subtype B versus non-B infection ( P  = 0.021). Conclusions: Compared with our previous studies, the proportion of NRTI- and first-generation NNRTI-related TDR has continued to decline in French seroconverters. However, subtype B-infected MSM could drive the spread of resistant HIV strains. Finally, we suggest preferring PI- or II- to NNRTI-based combinations to treat PHI patients.